We first : how brands and consumers use social media to build a better world - Mainwaring, Simon, 1967- (Palgrave Macmillan, 2011)
A social media expert with global experience with many of the world's biggest brands --including Nike, Toyota and Motorola--Simon Mainwaring offers a visionary new practice in which brands leverage social media to earn consumer goodwill, loyalty and profit, while creating a third pillar of sustainable social change through conscious contributions from customer purchases.